A study of correlation of expression of ER, PR and HER2/neu receptor status with clinico-pathological parameters in breast carcinoma at a tertiary care centre - Devi, P. Urmila; Prasad, Uma; Lakshmi, A. Bhagya; Rao, G. Santa (International Journal of Research in Medical Sciences, 2017)
Background: In English literature it is documented that the expression of ER and PR is low in Asian countries when compared to that of Western countries. HER2/neu over expression is uniform throughout the world. Studies have shown that triple-negative breast carcinomas are aggressive, likely to spread beyond the breast and recur after treatment. Aims and objectives: To correlate the expression of ER, PR and HER 2/neu with clinico-pathological parameters in infiltrating ductal carcinoma and other variants of breast carcinoma. To determine the clinicopathological parameters in triple negative cases. Methods: This is a prospective study for a period of two years in the Department of Pathology, Andhra Medical College, a tertiary care centre. We received 111 mastectomy specimens during this period out of which 52 patients were funded under Arogyasri and were subjected for ER, PR, HER2/neu receptor study. Results: In the present study total cases analyzed were 52. Infiltrating ductal carcinoma was 41/52 (78.84%) and other variants were 11/52 (21.15%). In our institute infiltrating duct cell carcinoma (NOS) type was the commonest type of carcinoma breast with significant group occurring in less than 45 years of age, 95 % of women were multipara with two or more children and triple negative tumors being 54.83%.In infiltrating ductal carcinoma ER, PR positive expression has no association with age and size of tumor. Their expression was higher in grade 1 tumors 83.3%.The ER,PR negative expression was more in size of tumor being greater than 2 cm; (92.5%),positive lymph nodes (51.8%) and stage II and stage III tumors (96.2%). HER2/neu negative expression was seen in 51.61% of cases. Triple negative receptor expression was seen in 54.83% of infiltrating ductal carcinoma. In the English literature medullary carcinoma is negative for HER2/neu expression but in the present study in 2 cases the expression for HER2/neu was positive. Conclusion: In the present study significant group occurred in less than 45 years of age presenting in advanced stage of the disease. Triple negative cases were seen in 54.8% cases of infiltrating duct cell carcinoma indicating bad prognosis.